KAJIAN SUHU DAN LAMA PEMASAKAN TERHADAP MUTU PERMEN SUSU KERBAU - Saputrayadi, Adi; Marianah, Marianah; Alia, Jannatun (Journal of Agritechnology and Food Processing, 2021)
The purpose of this study is to determine what temperature and cooking time is right to produce good quality milk candy and has a longer shelf life. The method used in this research is experimental method and the design used is a completely randomized design (CRD) with 2 factors. The first factor is the cooking temperature which consists of 3 levels (1100C, 1150C and 1200C). The second factor was the cooking time which consisted of 2 levels (60 minutes and 90 minutes). The stages of this research consisted of: (1) The process of making buffalo milk candy, (2) testing the chemical properties (moisture content and reducing sugar), (3) analyzing the organoleptic properties of buffalo milk candy. Based on the analysis, the temperature and cooking time had a significant effect on the chemical properties (moisture content and reducing sugar) and organoleptic properties (color and texture) of buffalo milk candy, but did not significantly affect the organoleptic properties (aroma and taste) of buffalo milk candy. The best treatment for the analysis of chemical and organoleptic properties was obtained in the S3L2 treatment (temperature 1200C, cooking time 90 minutes) with a water content of 2.969%, a reduced sugar content of 12.08%, a taste score of 4.00 (sweet criteria), a texture score of 3.20. (hard criteria), flavour score 4.25 (like criteria) and 2.35 color score (dark brown criteria).